Investigating Histopathologic the Synergistic Effect of Topical use of Mentha pulegium Essential Oil and Honey in Healing of Cutaneous Ulcers - Alireza Takzaree; Mehrdad Goodarzi; Tayebeh Rastegar; Shakiba Shahbabae; Nasrin Takzaree (Institue of Medicinal Plants, ACECR, 2019)
Background: Open skin lesions cause many problems for the health and the economy of societies in recent years, importance and effectiveness of traditional and complementary medicine have been increased. Objective: So this study was performed to investigate the synergistic effect of topical use of Mentha pulegium essential oil and honey in healing of cutaneous ulcers in rats. Method: This experimental study was performed on 75 healthy wistar male rats. Under anesthesia, a 1.5 * 1.5 mm full thickness square wound was created. In the experimental groups, the surface of the wounds was covered once daily with peppermint, honey, a combination of them and phenytoin ointment. No treatments were performed on the wounds of the control group. For histological studies, using staining (H & E) wound surface and wound healing were evaluated. Data were analyzed by using one-way ANOVA with post hoc Tukey test and P < 0.05 was significant. Results: The results of microscopic study showed histological parameters in wounds bed in the experimental group were significantly different from the control group. Generally, rats treated with honey or mint, or the combination of them, had higher percentage of wound healing and less wound surface, than negative and positive controls groups (P<0.05). Also, combination of honey and peppermint, was more effective than them alone. Conclusion: The results indicated percentage of wound healing and wound surface, topical use of Mentha pulegium essential oil and honey is effective in healing rat skin ulcers. Also, the synergistic effect of these two agents to accelerate wound healing has been proved.